2022
DOI: 10.3390/agriculture12091361
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Characterization of Bionic Mechanical Harvesting of Tea Buds

Abstract: To date, mechanized picking of famous tea (bud, one bud one leaf) causes a lot of damage. Manual picking results in high-quality tea but the process is inefficient. Therefore, in order to improve the quality of mechanically harvested tea buds, the study of bionic picking is beneficial to reduce the damage rate of mechanical picking. In this paper, the manual flexible picking process is studied, and a bionic bladeless mechanical picking mechanics model is developed. The relationship between the mechanical prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Therefore, the picking knife should be replaced in future research by a simulated manual lifting. Stem breakage but not leaf breakage was observed depending on the different breaking forces of the leaf and shoot stalks ( Luo et al., 2022 ). A picker requires high control accuracy when picking.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the picking knife should be replaced in future research by a simulated manual lifting. Stem breakage but not leaf breakage was observed depending on the different breaking forces of the leaf and shoot stalks ( Luo et al., 2022 ). A picker requires high control accuracy when picking.…”
Section: Resultsmentioning
confidence: 99%
“…The improvement of picking quality and efficiency is very important if we want to replace manual labor and achieve accurate picking in the future. Luo et al (2022) showed that when tea buds were picked by mechanical cutting, the wound surface was uneven, oxidation was severe, and the picking quality was inferior to manual picking. However, soft-bodied robots have flexibility, perception, and softness (Wang H. et al, 2018;Su et al, 2022) and are expected to be an effective method for picking tea buds in the future.…”
Section: Accurate Picking and Collection Of Tea Budsmentioning
confidence: 99%
“…cos n xx a a  = (7) where: ax is the acceleration of the pot groove under reciprocating motion (mm/s 2 ); η is the angle between the acceleration of the pot groove's motion and the tangential vector t (º); and θ is the angle between the acceleration of the pot groove's motion and the normal vector n (º).…”
Section: Fig 3 -Force Analysis Diagram Of Tea Particle Tossing Motionmentioning
confidence: 99%